2014
DOI: 10.1128/jcm.00921-14
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of an Acinetobacter baumannii Clonal Complex during Colonization of Patients

Abstract: Acinetobacter baumannii has emerged as one of the leading pathogens causing hospital-acquired infection. The success of A. baumannii as a pathogen has to a large extent been attributed to its capacity to remodel its genome. Several major epidemic clonal complexes of A. baumannii spread across different health care facilities around the world, each of which contains a subset of diversified strains. However, little is known about the population dynamics during colonization of A. baumannii within hosts. Here, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
0
23
2
Order By: Relevance
“…Our threshold value was also in agreement with sequencing of distinct isolates from the same patient in our ICU outbreak; such isolates had a maximum difference of 1 SNP, demonstrating that A. baumannii accumulated SNPs slowly over the time frame of an intrahospital outbreak. In contrast to our results, some studies have identified greater SNP differences between A. baumannii isolates recovered at different times from the same patient (106,107). In one study (107), the authors detected SNPs via alignment to a reference genome, followed by SNP filtering based on a "probability score."…”
Section: Figcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our threshold value was also in agreement with sequencing of distinct isolates from the same patient in our ICU outbreak; such isolates had a maximum difference of 1 SNP, demonstrating that A. baumannii accumulated SNPs slowly over the time frame of an intrahospital outbreak. In contrast to our results, some studies have identified greater SNP differences between A. baumannii isolates recovered at different times from the same patient (106,107). In one study (107), the authors detected SNPs via alignment to a reference genome, followed by SNP filtering based on a "probability score."…”
Section: Figcontrasting
confidence: 99%
“…In contrast to our results, some studies have identified greater SNP differences between A. baumannii isolates recovered at different times from the same patient (106,107). In one study (107), the authors detected SNPs via alignment to a reference genome, followed by SNP filtering based on a "probability score." Alignment-based methods can result in false-positive SNP calls.…”
Section: Figcontrasting
confidence: 99%
“…This is the first time that sequential outbreaks within a single hospital have been reported in which the second outbreak represents a recombinant with the original outbreak strain as a parent. Previously, several studies described that A. baumannii hospital outbreaks can be polyclonal, and a variety of recombination and horizontal gene transfer events occurred in A. baumannii strains and contributed to the genetic diversity in the microorganism, even among colonized patients (49)(50)(51)(52). Horizontal gene transfer that occurs between sampled and unsampled A. baumannii isolates may explain discrepancies between NGSbased SNV typing and PFGE typing results, as was seen here (13).…”
Section: Discussionmentioning
confidence: 78%
“…Microscale genome modification has been revealed through the analysis of single nucleotide polymorphisms (SNPs) between A. baumannii strains isolated from the same patient. This modification can lead the emergence of resistance and to different sequence typing by modifying a single allele [10]. However, this explanation cannot be applied to our case, because ST2 and ST25 have only two common alleles.…”
Section: Discussionmentioning
confidence: 91%